Assessing the fire behavior of woods modified by N‐methylol crosslinking, thermal treatment, and acetylation. (17th February 2020) - Rabe, Sebastian; Klack, Patrick; Bahr, Horst; Schartel, Bernhard
Summary: Wood products are often treated by different techniques to improve their longevity when used as building materials. Most of the time, the goal is to increase their resistance to weathering effects, deformations in material dimensions or biotic decomposition. These wood treatment techniques have a significant impact on pyrolysis and burning behavior. The general effects of three different common wood treatments on flame retardancy were investigated by comparing treated woods with their untreated counterparts and with other kinds of wood. While the acetylation of beech leads to a slightly increased fire hazard, the thermal treatment of wood and crosslinking of cellulose microfibrils dimethyloldihydroxy‐ethyleneurea show a limited flame retarding effect. Switching to woods with a higher lignin content, and thus higher char yield, however, results in a more pronounced improvement in flame retardancy performance. This article delivers a comprehensive and balanced assessment of the general impact of different wood modifications on the fire behavior. Further, it is a valuable benchmark for assessing the flame retardancy effect of other wood modifications.